Stamp collecting get stuck into stamps. ([Australia] : Australia Post, 1975)
Poster features an elaborate scroll-design containing the titles across the top and foot of the poster. Main illustration shows a simplified, cartoon-style illustration of a smiling pink-faced man sticking stamps into a book, above photographs of several different Australian stamps produced in the 1970s. Stamps are arranged on a bright yellow background with accompanying text.
"P is for philately".
Catalogue record generated as part of a batch load.
Also available online
Keywords: Australia Post -- Posters; Postage stamps -- Australia -- Posters; Stamp collecting -- Australia -- Posters